Mixomas Cardíacos, 13 Anos de Experiência no seu Diagnóstico Ecocardiográfico - Oliveira, R (2011)
INTRODUCTION: Transthoracic echocardiography is the method of choice for the diagnosis of cardiac myxomas, but the transesophageal approach provides a better definition of the location and characteristics of the tumor. The authors review their thirteen years' experience on the echocardiographic diagnosis of this pathology. METHODS: From 1994 to 2007, 41 cardiac tumors were diagnosed in our echocardiographic laboratory, of which 27 (65.85%) were cardiac myxomas. The exams and the patients' clinical files were retrospectively reviewed. RESULTS: Of the 27 patients, 22 (81.5%) were female, with a mean age of 62.1 +/- 13.6 years (25-84 years). The predominant clinical features were due to the obstruction caused by the tumor in more than two thirds of the patients, followed by constitutional symptoms in one third and embolic events in 30%. In the lab results, anemia was found in three patients and elevated sedimentation rate and CRP in two. In two patients the myxoma was found by chance. All the cases were of the sporadic type, although we found a prevalence of thyroid disease of 14% (4 patients). All patients underwent urgent surgical resection except one, in whom surgery was refused due to advanced age and comorbidities. The myxomas followed a typical distribution with 24 (88.8%) located in the left atrium, 18 of them attached to the atrial septum (AS) and two to the mitral valve. In one patient, the tumor involved both atria. The other two cases originated in the right atrium at the AS. Embolic phenomena were more frequent in small tumors (p = 0.027) and in those with a villous appearance (p = 0.032). Obstructive manifestations were associated with larger tumors (p = 0.046) and larger left atria (p = 0.048). In our series, there were no deaths during hospitalization or in the follow-up period of 5.2 +/- 3.7 years in 19 patients. There were two recurrences, both patients being successfully reoperated. CONCLUSION: Myxoma is the most common cardiac tumor. Transesophageal echocardiography provides excellent morphologic definition, aiding in diagnosis and follow-up. Most clinical manifestations are obstructive and are associated with larger tumors. Small tumors with a friable appearance have a higher chance of embolization. Surgical resection is usually curative and the long-term prognosis is excellent.